Effects of different intensities of endurance exercise on oxidative stress and antioxidant capacity - Masaki Takahashi; Katsuhiko Suzuki; Hideki Matoba; Shizuo Sakamoto; Shigeru Obara (Japanese Society of Physical Fitness and Sports Medicine, 2012)
The purpose of this study was to investigate the effects of three different intensities of exercise on oxidative stress and antioxidant capacity. Eight healthy male subjects performed three different intensities of exercise for 20 minutes: (1) 70% anaerobic threshold (AT) (light intensity, LI), (2) 100% AT (moderate intensity, MI), and (3) 130% AT (high intensity, HI) on a cycle ergometer. A control (C) trial was conducted under resting conditions. Blood samples were taken pre-exercise, immediately and 30 min after exercise. In the HI trial only, the concentrations of plasma derivatives of reactive oxygen metabolites (d-ROMs) were significantly higher immediately (P<0.01) and 30 min after exercise (P<0.05) than at pre-exercise. Furthermore, plasma trolox equivalent antioxidant capacity was significantly higher immediately after exercise in the HI trial (P<0.01). And, plasma glutathione peroxidase (GPX) activity was significantly higher immediately after exercise than at pre-exercise in the MI (P<0.05) and HI trials (P<0.01). These data suggest that 20 min of pedaling exercise above the AT level may increase ROS production, while endogenous enzyme activity (especially GPX activity) or non-enzymatic antioxidants may modulate exercise-induced ROS generation. Thus, exercise under the AT level induces very little oxidative stress damage in young people.